Osimertinib compared docetaxel-bevacizumab as third-line treatment in EGFR T790M mutated non-small-cell lung cancer. (July 2018) - Nie, Keke; Zhang, Zhongfa; Zhang, Chunling; Geng, Chuanxin; Zhang, Ling; Xu, Xiajuan; Liu, Shichao; Wang, Songping; Zhuang, Xingjun; Lan, Ketao; Ji, Youxin
Highlights: Represented the First phase 3 trial of osimertinib of 3rd line therapy on EGFR T790M positive NSCLC. Osimertinib was the optimal third-line treatment for NSCLC patients harboring EGFR T790M. The results of TKI-chemotherapy or chemotherapy-TKI treatment sequential used were equal. Abstract: Objective: To compare the efficacy and toxicity of osimertinib versus docetaxel-bevacizumab as third-line treatment in EGFR T790M mutated NSCLC. Methods: In this phase 3, open-label, three-center study, we randomly assigned (1:1) previously treated with TKI-chemotherapy or chemotherapy-TKI recurrent or metastatic advanced non-squamous lung cancer patients into two groups. These patients had acquired EGFR T790M resistance mutation confirmed by tumor tissues or serum. One group received oral osimertinib (80 mg/day) and the other group received intravenous infusion docetaxel (75 mg/m 2 ) and bevacizumab (7.5 mg/kg) every 21 days until disease progression, unacceptable toxic effects or patient death. The primary endpoint of this study was progression-free survival (PFS) and the secondary endpoints were response rates, toxicities and overall survival (OS). This trial was registered with ClinicalTrials.gov, number NCT02959749. Results: A total of 147 patients were treated. Among them, 74 were enrolled in the osimertinib group and 73 were in the docetaxel-bevacizumab group. The median progression-free survival was 10.20 months in the osimertinib group versus 2.95 months in the docetaxel-bevacizumab group (hazard ratio 0.23; 95% confidence interval [CI], 0.12–0.38; P < 0.001). The overall response rate in the osimertinib group was significantly better than in the docetaxel-bevacizumab group (61.6%; 95% CI, 55.5–67.7 versus 8.3%; 95% CI, 1.3–15.3; p < 0.001). Because all the progressed patients in the docetaxel-bevacizumab group crossed over to the osimertinib group, there was no significant difference in the median OS between two groups at the time of last follow-up (hazard ratio 0.79; 95% CI, 0.38–1.61; P = .551). The main grade 3 or 4 toxic effects were diarrhea (2.7%) and interstitial lung disease (1.4%) in the osimertinib group and alopecia (15.3%), anorexia (12.5%), neutropenia (9.7%) and nausea (8.3%) in the docetaxel-bevacizumab group. Conclusions: Osimertinib had higher response rate, longer PFS and milder side effects than docetaxel-bevacizumab in third-line therapy in patients with EGFR T790 M positive advanced NSCLC.